Networks, SMEs, and the university : the process of collaboration and open innovation - Johnston, Andrew; Huggins, Robert (Edward Elgar Publishing, 2021)
"Exploring the process of university collaboration from the perspective of small- and medium-sized enterprises (SMEs), this book offers an in-depth examination of the collaboration process, dispelling the myth of the disengagement of these firms. Andrew Johnston and Robert Huggins present a thorough account of how SMEs can 'unlock the ivory tower' and gain access to university knowledge to support their own innovation. Outlining and discussing the intellectual roots of research in this field in an accessible way, the book focuses on SMEs to provide insight to an often overlooked group of firms. Chapters show how the closeness of the partners in terms of network membership, working culture and practice, and technical language drive the formation and function of these collaborative links, offering a holistic account of this from idea generation to the completion of projects. This will be an essential read for academics researching innovation and the role of universities, as well as knowledge exchange practitioners wishing to further their understanding of collaboration processes. Policymakers seeking to explore how and why SMEs engage in open innovation practices will also find this an invigorating book"--